Neuropoly: An Educational Board Game to Facilitate Neurology Learning - Raskurazhev, Anton; Kuznetsova, Polina; Khizhnikova, Anastasia Evgenievna; Klochkov, Anton; Bakulin, Ilya; Annushkin, Vladislav; Tanashyan, Marine; Suponeva, Natalya; Gnedovskaya, Elena (Frontiers in Systems Neuroscience, 2021)
Introduction: Neurology is arguably one of the most difficult subjects to teach and study in the medical curriculum. Educational games (EG) may be a valid option to enhance motivation in neurology residents. Methods: We developed an educational board game (Neuropoly) to assist in teaching neurology. We present here an overview of the game, as well as the results of a pilot study aimed at determining: a) the efficacy of the game in teaching certain neurological concepts; b) student compliance and satisfaction with the EG. Results: The pre- and post-play questionnaire scores differed significantly (3.2 ± 1.7 vs 7.8 ± 1.6, p < 0.001). Our group of residents, showing an overwhelmingly positive response, very well received the game. The questions were rated as above average regarding difficulty. Conclusion: The ‘Neuropoly’ educational board game has been shown to be interesting, efficient and motivational among first- and second-year neurology residents. Novel educational methods for complex medical disciplines should be developed, with board games being a viable and inexpensive approach.